Moderating role of triglycerides in the relationship between amyloid-β, hippocampal atrophy, and cognitive decline in mild cognitive impairment and early Alzheimer’s disease - Ji-Woo Seok; Kahye Kim; Soonjo Hwang; Kun Ho Lee; Kun Ho Lee; Kun Ho Lee; Jaeuk U. Kim; Jaeuk U. Kim (Frontiers in Aging Neuroscience)
IntroductionThe role of triglycerides in Alzheimer’s disease dementia (ADD) progression remains unclear. This study aimed to investigate how triglyceride levels influence the relationship between amyloid-beta (Aβ) deposition, hippocampal atrophy, and cognitive decline in individuals with mild cognitive impairment (MCI) and early-stage ADD.MethodsA total 188 older adults (170 with MCI, 18 with early ADD) from the Gwangju Alzheimer’s Disease and Related cohort underwent amyloid PET and structural magnetic resonance imaging. Cognitive decline was assessed using the Korean version of the Mini-Mental State Examination (K-MMSE). A moderated mediation model (PROCESS model 7 with 10,000 bootstrap samples) was applied to examine whether hippocampal atrophy mediated the effect of Aβ on cognitive decline and whether this effect varied by triglyceride levels.ResultsThe indirect effect of Aβ deposition on cognitive decline through hippocampal atrophy was significant (bootstrap 95% CI: −0.39 to −0.08), while the direct effect was not. This suggests that hippocampal atrophy plays a substantial mediating role in the pathway from Aβ burden to cognitive decline, although the indirect path accounted for approximately 49% of the total effect, indicating the possibility of other unexplored mechanisms. Furthermore, moderated mediation analysis revealed that triglyceride levels significantly moderated the effect of Aβ deposition on hippocampal volume (p < 0.05), with higher triglyceride levels amplifying the negative impact of Aβ deposition on hippocampal atrophy.DiscussionThese findings highlight hippocampal atrophy as a key pathway linking Aβ burden to cognitive impairment. Moreover, higher triglyceride levels may exacerbate Aβ-related neurodegeneration in individuals with MCI and early-stage ADD. Metabolic risk factors, such as triglycerides, may play an important role in strategies to prevent or delay cognitive decline in older adults with MCI and early ADD.